Leaf fatty acid composition of some Lamiaceae taxa from Turkey - Cacan, Erdal; Kokten, Kagan; Kilic, Omer (Progress in Nutrition, 2018)
Fatty acids composition leaves of Satureja hortensis L., Satureja boissieri Hausskn ex Boiss., Thymus kotschyanus Boiss.& Hohen. var. glabrescens Boiss., Thymus kotschyanus Boiss. & Hohen. var. kotschyanus, Thymus hausknechtii Velen., Thymus pubescens Boiss. & Kotschy ex Čelak var. pubescens, Thymus fallax Fisch & Mey, Origanum vulgare L. subsp. gracile and Origanum acutidens L., were analyzed by gas chromatography. The fatty acid composition of plants used to this study showed different saturated and unsaturated fatty acid concentrations. The main fatty acids found were Palmitic acid methyl ester (13.49-27.71%), Linoleic acid methyl ester (10.85-19.47%), and Linolenic acid methyl ester (40.68-56.53%); while other fatty acids were found in minor proportions. As a result, all taxa had the highest total unsaturated fatty acid amounts (39.05-73.19%) and the lowest total saturated fatty acid amounts (19.43-51.12%). The highest unsaturated fatty acid determined to Satureja hortensis (73.19%), the lowest to Thymus hausknechtii (39.05%). In this study, palmitic acid methyl ester was found the major saturated fatty acids in all studied taxa.